Synthesis of Nano-Structured HgS by Sol-Gel - Kharghanian, Leila; Moghimi, Ali (Asian Journal of Chemistry, 2013)
The main focus is laid on the sol-gel synthesis is opening a wide window toward nano-scopic metal sulfides with remarkable properties different from that of crystalline metal sulfides. Nanocomposites HgS/SiO2 has been prepared by the sol-gel method starting from methyltriethoxysilane (MTEOS) precursors as the SiO2 sources and mercaptopropyltrimethoxysilane (MPTMS) as the capping agent. The average diameter of HgS particles in the nano-composite materials can be controlled by the cadmium concentration and thermally treatment. The dried gel was treated at increasing temperatures, The crystallinity, shape and size of the metal sulfide nanocrystals were investigated by X-ray diffraction and transmission electron microscopy. The result indicates that the formation and the stability of the mercury sulfide phases are strongly affected by the precursors used as the mercury sources.